Ah Louis Bricks
Photo of men and horses working in a brickyard. Caption reads: 'Ah Louis bricks were originally made by crude methods with clay-dirt from the hillside of the San Luis Mountain. But the product proved to be strong and durable for numerous structures built about the turn of the century in the City of San Luis Obispo, have withstood severe storms, and the ravages of the elements and earthquakes. They were eventually deliberately torn down due to building restrictions. Some of these were the old Andrews Hotel, the original county courthouse, the Southern Pacific Railroad Roundhouse, the east wing of the Old Mission Church, and the El Monterey- Obispo Theatre building. Still standing and still being used is the original Sperry Flour Company building (now the Furniture Warehouse and Sport Shop), nearly all of the Andrews Bank block, Sinsheimer Bros. Store and the Ah Louis Store.'